Usability of MOOC developing higher order thinking skills (HOTS) in fiction classes - Tengku Nur Amira Solehah Tengku Anuar (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This paper explores the usability of a MOOC entitled Integrating HOTS into Literature Integrated Language Classrooms which was created to develop students' higher order thinking skills (HOTS) through the use of fiction in language classes. Although MOOCs have been a growing phenomenon in higher education around the world, its usability is still debatable and there has been little research done to assess it. In this study, a mixed-method approach was employed by distributing an adapted usability questionnaire and conducting individual interview sessions. Thirty English language teachers from ten secondary schools in Kuala Terengganu district were involved. The adapted usability questionnaire was developed to evaluate the usability of the MOOC from four dimensions including learnability, efficiency, effectiveness, and satisfaction. The data was later analysed using SPSS to get descriptive statistics. To obtain qualitative data, individual interview sessions were conducted with ten teachers who had used the MOOC in the classroom to gain a detailed understanding of their perceptions towards the MOOC and the impact of the MOOC on their students' development of HOTS. The data from the interviews were analysed using thematic analysis method. Analyses of the quantitative and qualitative data revealed that the teachers: 1) agreed on the usability of the MOOC in regard to three specific constructs namely learnability, effectiveness, and satisfaction, 2) gave positive responses to the MOOC, highlighted some weaknesses of the MOOC, and suggested a few recommendations for improvement, and 3) perceived that the use of HOTS activities provided in the MOOC has given a positive impact on their students' critical thinking skills. Therefore, it can be concluded that the MOOC can be a useful platform for the language teachers to stimulate their students' critical thinking skills in fiction classes.